2017
DOI: 10.1126/scitranslmed.aal2144
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of potent HIV-1 broadly neutralizing antibodies and antibody-sensitive viruses in a viremic controller

Abstract: Some HIV-1–infected patients develop broad and potent HIV-1 neutralizing antibodies (bNAbs) that when passively transferred to mice or macaques can treat or prevent infection. However, bNAbs typically fail to neutralize coexisting autologous viruses due to antibody-mediated selection against sensitive viral strains. We describe an HIV-1 controller expressing HLA-B57*01 and HLA-B27*05 who maintained low viral loads for 30 years after infection and developed broad and potent serologic activity against HIV-1. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
167
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(186 citation statements)
references
References 108 publications
(213 reference statements)
19
167
0
Order By: Relevance
“…Quaternary interactions visualized thus far for V1V2 bNAbs involve the binding of a single Fab to the apex of Env trimer (Julien et al, 2013b; Liu et al, 2017), but here we demonstrate that the stoichiometry of binding for the new V1V2 bNAb BG1 (Freund et al, 2017) is two Fabs per Env trimer, with a minor population of 3:1 BG1-Env complexes (Figures 2 and 3; Figure 3—figure supplement 1). …”
Section: Discussionsupporting
confidence: 50%
“…Quaternary interactions visualized thus far for V1V2 bNAbs involve the binding of a single Fab to the apex of Env trimer (Julien et al, 2013b; Liu et al, 2017), but here we demonstrate that the stoichiometry of binding for the new V1V2 bNAb BG1 (Freund et al, 2017) is two Fabs per Env trimer, with a minor population of 3:1 BG1-Env complexes (Figures 2 and 3; Figure 3—figure supplement 1). …”
Section: Discussionsupporting
confidence: 50%
“…By directly tying the presence of B cells and neutralizing antibodies to maintenance of steady-state plasma viremia, these studies suggest that the humoral immune response helps to establish and preserve a balance between host and HIV/SIV. Lastly, while natural control of viremia is considered to be mediated mostly by CD8 T cells, humoral immunity may contribute in certain cases [115,116]. In summary, antibodies put significant pressure on the virus and appear to play a role in maintaining at least partial control of HIV viremia.…”
Section: T-bet+ B Cells: Contributing Members Of the Antiviral Resmentioning
confidence: 99%
“…Recently, Koofhethile et al [5] demonstrated that viremic controllers (VCs) not carrying ‘protective’ alleles of HLA-B genes control HIV-1 infection more robustly than carriers, and that CD8 + T cells do not mediate this effect. In addition, Freund et al [6] demonstrated that HIV-1 Env-specific antibodies with broad neutralising activity might have contributed to long-term control of HIV-1 infection in an elite controller (EC) who carried the ‘protective’ HLA-B alleles HLA-B*57:01 and HLA-B*27:05. However, the findings of previous studies on the role of antibodies in the natural control of HIV-1 infection have been inconclusive [2, 711].…”
mentioning
confidence: 99%